An Analysis of Spatial Distribution of Urban Services with Focus on Social Justice and Emphasis on Citizens\' Satisfaction (Case Study: District 11 of Mashhad) - ahmad asadi; roghayeh kalateh meymari (تحقیقات کاربردی علوم جغرافیایی)
The present research is descriptive-analytical and in terms of its purpose. Data needed for research were collected by means of documentation (library, magazines) and field materials using a questionnaire. Using the Cochran formula, the sample size of the population was estimated at 383 people and the data were obtained using spatial analysis ArcGIS and SPSS software have been analyzed. In order to analyze the distribution of urban services, the index of access to urban services has been used, which is derived from land use plans of Mashhad city and municipal information and obtained from network analysis (ANP) and spatial statistics tests. Also, to assess the satisfaction of citizens from the distribution of urban services through a questionnaire and using one-sample T-test in spss software. Also, Gray Gray Analysis (GRA) method has been used for ranking the neighborhoods of the District 11 of Mashhad in terms of social justice. The final indicator of the distribution of urban services indicates the favorable distribution of urban services in the Daneshjo, sharif, Tarbiat, farhang, and parts of Azadshahr and Faroghottahsilan. As well as the neighborhoods of Ziba shahr, Shahid Razavi and parts of Faroghottahsilan and Azad shahr, they are in a disadvantaged position in terms of the distribution of urban services. Also, based on spatial self-correlation test, the pattern of indicators in the study area has spatial self-correlation and cluster pattern. The analysis of the distribution pattern of urban services in the District 11 of Mashhad using J statistics shows that the distribution of urban services in the study area has a high concentration of cluster patterns. Based on the analysis of the gray-matter analysis of daneshjo, Azad Shahr, farhang and Sharif neighborhoods, they have high levels of social justice, and other neighborhoods are ranked respectively. In the following, the results of t test indicate that among the neighborhoods, Daneshjo, Sharif, farhang, Tarbiat and Azad Shahr neighborhoods had the highest satisfaction with urban services. The neighborhood of Zibashahr has had the least satisfaction with the distribution of urban services. The results of all the models used in the paper are highly consistent and consistent.